Administrators’ Management Skills and School Performance of Zone II Division of Zambales - Roselle Salazar Umipig, Gail; N. Farin, Elizabeth (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The study aimed to assess the administrators’ management skills and schools’ performance of Zone II, Division of Zambales. Results of the study served as the basis in the development of an intervention program to enhance the administrator’s management skills in Zone II, Division ofZambales. The research design used in the study was descriptive and quantitative in its analysis. A typical school administrator has MA/MS units, rendered 25- 29 years of service and has attended nine and above relevant trainings in school management. Majority of the public elementary teachers are Teacher I, with MA/MS units and have rendered five to nine years in service. The assessment of the administrators strongly agree on the administrator’s human, conceptual and technical skills. The assessment of the teachers strongly agree on the administrators’ human, conceptual and technical skills. The school performance in the last school year 2018- 2019 in Zone II, Division of Zambales was Outstanding. There was a significant difference on the on the Administrators’ Technical Skill as assessed by the administrators when grouped according to the highest educational attainment. There was a significant difference on the Administrators’ Conceptual Skill, Human Skill and Technical Skill as assessed by the teachers when group according to designation. There was a significant difference on the Administrators’ conceptual skill, human skill and technical skill as assessed by the Administrators and Teachers. There was a very low positive correlation between the assessment of the administrators on the level of administrator’s conceptual skill and school performance in the school year 2018-2019 in Zone II, Division of Zambales. There was a very low negative correlation between the assessment of the administrators on the level of administrators’ human skill, technical skill and school performance in the school year 2018- 2019 in Zone II, Division of Zambales. There is a high positive correlation between the assessment of the teachers on the level of administrator’s management skills and school performance in the last school year 2018-2019 in Zone II, Division of Zambales. There was a very high positive correlation between the assessment of the teachers on the level of administrator’s conceptual skill, technical skills and school performance.